Biofunctional gelatin-based films incorporated with food grade phycocyanin extracted from the Saharian cyanobacterium Arthrospira sp. (April 2019) - Chentir, Imene; Kchaou, Hela; Hamdi, Marwa; Jridi, Mourad; Li, Suming; Doumandji, Amel; Nasri, Moncef
Abstract: Biofunctional films based on bovine gelatin (G) incorporated with a food grade phycocyanin (PC) extract at various concentrations (1.25%, 2.5%, 6.25% and 12.5%; w/w) were developed. PC incorporation maintained the original solubility of gelatin (control) film, while, when added at 6.25% and 12.5% (w/w), PC decreased the L* and increased b*, ΔE and the opacity values of the films, which enhances their light-barrier feature. Further, the tensile strength (TS) and elongation at break (EAB) were reduced with the increase of PC content in G-based films, and were inversely correlated to films thickness with respective R 2 values of 0.94 and 0.97. Regarding microstructure, PC eliminated cracks present in the control film matrix resulting in a more smooth structure. Moreover, PC addition contributed to the thermal stabilization of the gelatin chain, delaying the glass transition temperature by 20 °C and conferring a thermal stability up to 250 °C. Regarding the antioxidant activity, the incorporation of 12.5% of PC significantly increased by 4.09, 3.2, 13.6 and 1.47-folds the chelating, reducing, β-carotene bleaching inhibition and DPPH radical scavenging capacities, respectively. Likewise, G-PC films displayed antibacterial activity against several Gram (−) and Gram (+) bacteria. The present study suggested that G-PC films incorporated with 6.25% and 12.5% of PC extracted from Arthrospira sp. could be used as a promising colored external or inner (secondary) functional packaging for dehydrated food products as well as for hard or soft-shelled capsules containing powdered or oily active ingredients, although further analysis should be carried out. Graphical abstract: Highlights: Gelatin-based films incorporated with phycocyanin (G-PC) were developed. G-PC films presented soluble and light-barrier properties. Gelatin-based films thermal properties were enhanced with phycocyanin. Phycocyanin eliminated cracks and led to a smooth structure of Gelatin-based film. G-PC films exhibited interesting antioxidant and antibacterial activities.